Diagnosing ovarian cancer by identifying SCC‐antigen on a multiwalled carbon nanotube‐modified dielectrode sensor. (12th September 2019) - Liang, Ting; Qu, Qiuzhi; Chang, Yuhua; Gopinath, Subash Chandra Bose; Liu, Xian Tong
Abstract: Ovarian cancer starts in the ovaries in its earlier stages and then spreads to the pelvis, uterus, and abdominal region. The success of an ovarian cancer treatment depends on the stage of the cancer and the diagnostic system. Squamous cell carcinoma antigen (SCC‐Ag) is one of the most efficient cancer biomarkers, and elevated levels of SCC‐Ag in ovarian cancer cells have been used to identify ovarian cancer. Carbon is a potential material for biosensing applications due to its thermal, electrical, and physical properties. Multiwalled carbon nanotubes (MWCNTs) are carbon‐based materials that can be used here to detect SCC‐Ag. Anti‐SCC‐Ag antibody was immobilized on the amine‐modified MWCNT dielectric sensing surface to detect SCC‐Ag. The uniformity of the surface structure was measured with a 3D nanoprofiler, and the results confirmed the detection of SCC‐Ag at ∼80 pM. The specific detection of SCC‐Ag was confirmed with two control proteins (factor IX and human serum albumin), and the system did not show biofouling. This experimental set‐up with MWCNTs a dielectric sensing surface can lead to the detection of ovarian cancer in its initial stages.